WCOM (World Class Operations Management) Why You Need More Than Lean - Baroncelli, Carlo; Ballerio, Noela; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book deals with World Class Operations Management (WCOM), detailing its principles, methods and organisation, and the results that this approach can bring about. Utilising real-world case studies illustrated by companies that have adopted this model (interviews with Saint-Gobain, L'Oréal, Tetra Pak, Bemis, and Bel Executives), it describes common patterns drawn from decades of hands-on experience, so as to present a theoretical approach together with the concrete application of its principles. WCOM, adopted by several multinational companies, is one of the more innovative management practises, as it integrates the best Continuous Improvement approaches (Lean, Total Productive Management, World Class Manufacturing) as well as the most innovative approaches in human dynamics like Change Leadership, Performance Behavior, Shingo Model, to name a few. Maximising reader insights into the successful implementation of such an approach, and explaining not only itspotentialities, but also its implementation dynamics, the critical points and the ways it can be integrated into different situations, this book is also about how to create a culture of excellence that is sustainable over a long period of time and delivers consistent (or ever-improving) results.
Preface -- Foreword -- Introduction -- Part 1. Cases and Best practices -- 1.1 The Bel Boost case -- 1.2 The Bemis WCM case -- 1.3 The L'Oréal WCM case -- 1.4 The Saint-Gobain WCM case -- 1.5 The Tetra Pak WCM case -- Part 2. The WCOM™ Model -- 2.1Intro to WCOM™, why & what: the loss concept -- 2.2Strategy Deployment -- 2.3 The three phases of WCOM™ -- 2.4 The WCOM™ Organisation -- 2.5 WCOM™ in Research and Development -- 2.6 WCOM™ in Supply Chain -- 2.7 WCOM™ in Procurement -- 2.8 WCOM™ in Business Process -- 2.9 Implementation -- 2.10 History of TPM and JIPM: The TPM Awards from the Japan Institute of Plant -- Part 3. The Human side -- 3.1The human dynamics in WCOM™ -- 3.2Change management and leadership -- 3.3Performance Behavior -- 3.4The Shingo Model -- 3.5TWI -- 4. Conclusion -- 4.1Key Patterns of a Common Approach -- Annex: the Value Chain Pillars in brief -- About the authors -- Acknowledgements.
Keywords: Industrial Management; Industrial organization; Operations research; Management science; Industrial Management; Industrial Organization; Organization; Operations Research, Management Science